Neuroprotective and anti-inflammatory effects of lidocaine in kainic acid-injected rats. Issue 7 (4th May 2016) - Chiu, Kuan Ming; Lu, Cheng Wei; Lee, Ming Yi; Wang, Ming Jiuh; Lin, Tzu Yu; Wang, Su Jane
Abstract : Lidocaine, the most commonly used local anesthetic, inhibits glutamate release from nerve terminals. Given the involvement of glutamate neurotoxicity in the pathogenesis of various neurological disorders, this study investigated the role of lidocaine in hippocampal neuronal death and inflammatory events induced by an i.p. injection of kainic acid (KA) (15 mg/kg), a glutamate analog. The results showed that KA significantly led to neuronal death in the CA3 pyramidal layers of the hippocampus and this effect was attenuated by the systemic administration of lidocaine (0.8 or 4 mg/kg, i.p.) 30 min before KA injection. Moreover, KA-induced microglia activation and gene expression of proinflammatory cytokines, namely, interleukin-1β, interleukin-6, and tumor necrosis factor-α, in the hippocampus were reduced by the lidocaine pretreatment. Altogether, the results suggest that lidocaine can effectively treat glutamate excitotoxicity-related brain disorders.